O Estado da arte à luz da teoria dos registros de representação semiótica: um olhar sobre as produções acadêmicas brasileiras - Tiburtino, Adriana Ferreira (2021)
This research aims to present the State of the Art of Brazilian academic productions developed between 2013 and 2018 that use Raymond Duval's Theory of Semiotic Representation Records as a theoretical input. According to the author, we can use in Mathematics a great variety of registers of semiotic representations (Graphics, Algebraic Representation, Tables, Mother Tongue, among others) to treat mathematical concepts, thus diversifying the various modes of access of students to mathematical content. The data collection was done through the bibliographic survey of theses and dissertations that are inserted in the CAPES (Commission for the Improvement of Higher Level People) thesis bank. Our research is based on a documental study called Estado Arte (State of Art), where we seek to understand and present the main perspectives around Duval's theory. This research has a bibliographic character which allowed us to have pertinent discussions about this area of knowledge, its constitution, its subjects, themes addressed and the methodological procedures applied in the research. By investigating the productions developed we came across 201 works that meet the selected parameters and helped us to constitute the corpus of our research. Initially, a general mapping was made, being analyzed the year, theoretical contribution, title of the work, institution of origin and the summaries in a quantitative way. And in a qualitative way, we carried out an in-depth reading of the research to ascertain specific information in order to categorize into focus and subfocuses the works registered. In this way, this research seeks to contribute, expand research around the Teaching of Science and Mathematics and promote a dialogue between academic studies and contemporary society.